Implementasi Kode Etik Insinyur dan Profesionalisme terhadap Signifikansi Metode Pelaksanaan dan Manajemen Proyek pada Proyek Konstruksi Rehabilitasi Laboratorium dan Lapangan SMPN 2 Kota Mojokerto - Rahmanita Nuzula; Ridho Bayu Aji; M. Sigit Darmawan; Budi Suswanto; RPX Rooswan Happmono (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
The implementation method and project management are important points in the running of this rehabilitation project. In accordance with the planning document, it is expected that the significance of planning and implementation does not have a much different percentage. The implementation method is the center of the formation of the plan until it becomes a new building after rehabilitation, as well as project management that focuses on time and quality control is also part of the implementation of the project. The results of the observation of engineering practices found that the percentage of building rehabilitation implementation methods that occurred in the field was 97.43%, while the percentage of field rehabilitation was 97.33%. So the total percentage of the overall work carried out against the plan is 97.38%. The results for time and quality management were obtained that from the 19th to the 20th week there was a delay in the work because in that week there was a material delay, this is known from the analysis of the daily report on the project. In completing the work according to the specified time is carried out with quality according to specifications, re-scheduling is carried out on certain work. From these results, it can be said that they are responsible for their profession which reflects the code of ethics of engineers as well as the ability to complete work well which reflects professionalism.